A global stocktake of the Paris pledges: Implications for energy systems and economy. (November 2016) - Vandyck, Toon; Keramidas, Kimon; Saveyn, Bert; Kitous, Alban; Vrontisi, Zoi
Highlights: This paper assesses the impact of the policies implied by the Paris Agreement. We exploit the complementarities between an energy model and an economic model. The Paris pledges mark a break from historic trends of greenhouse gas emissions. Energy systems across the globe will undergo a substantial transformation. Global climate change mitigation is consistent with robust economic growth. Abstract: The United Nations-led international climate change negotiations in Paris in December 2015 (COP21) trigger and enhance climate action across the globe. This paper presents a model-based assessment of the Paris Agreement. In particular, we assess the mitigation policies implied by the Intended Nationally Determined Contributions (INDCs) put forward in the run-up to COP21 by individual member states and a policy that is likely to limit global warming to 2 °C above pre-industrial levels. We combine a technology-rich bottom-up energy system model with an economy-wide top-down CGE model to analyse the impact on greenhouse gas emissions, energy demand and supply, and the wider economic effects, including the implications for trade flows and employment levels. In addition, we illustrate how the gap between the Paris mitigation pledges and a pathway that is likely to restrict global warming to 2 °C can be bridged. Results indicate that energy demand reduction and a decarbonisation of the power sector are important contributors to overall emission reductions up to 2050. Further, the analysis shows that the Paris pledges lead to relatively small losses in GDP, indicating that global action to cut emissions is consistent with robust economic growth. The results for employment indicate a potential transition of jobs from energy-intensive to low-carbon, service oriented sectors.